2023
DOI: 10.1002/adhm.202300970
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Precision Cell Electrospinning as an Efficient Stem Cell Delivery Approach for Cutaneous Wound Healing

Abstract: Mesenchymal stem cell (MSC) therapies have been brought forward as a promising treatment modality for cutaneous wound healing. However, current approaches for stem cell delivery have many drawbacks, such as lack of targetability and cell loss, leading to poor efficacy of stem cell therapy. To overcome these problems, in the present study, an in situ cell electrospinning system is developed as an attractive approach for stem cell delivery. MSCs have a high cell viability of over 90% even with a high applied vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, it also increased the expression of vascular endothelial growth factor (VEGF) and the formation of small blood vessels to promote angiogenesis but significantly reduced the expression of interleukin-6 (IL-6), and ultimately promoted skin wound healing [107]. When comparing poly (ε-caprolactone) (PCL) and poly (ε-caprolactone)/type I collagen (PCol) in the ability to promote biological signaling, wound coverage, and tissue repair processes, it was found that PCol/human Wharton's jelly mesenchymal stromal cells hWJ-MSCs had a better effect on skin tissue repair [108].…”
Section: Stem Cell Delivery Into Skin Woundsmentioning
confidence: 99%
“…Furthermore, it also increased the expression of vascular endothelial growth factor (VEGF) and the formation of small blood vessels to promote angiogenesis but significantly reduced the expression of interleukin-6 (IL-6), and ultimately promoted skin wound healing [107]. When comparing poly (ε-caprolactone) (PCL) and poly (ε-caprolactone)/type I collagen (PCol) in the ability to promote biological signaling, wound coverage, and tissue repair processes, it was found that PCol/human Wharton's jelly mesenchymal stromal cells hWJ-MSCs had a better effect on skin tissue repair [108].…”
Section: Stem Cell Delivery Into Skin Woundsmentioning
confidence: 99%
“…As the largest organ on the surface of the human body, the skin has the basic ability of thermoregulation, immunity, and resistance to external bacteria and viruses. , Deep burns resulting from high temperatures or electric shocks can lead to damage to both the epidermis and a portion of the dermis in the skin. It can cause intense pain and pose a significant threat to life if not promptly treated.…”
Section: Introductionmentioning
confidence: 99%
“…Wound dressings represent a current approach in the treatment of diabetic ulcers, encompassing film dressings, 21,22 electrospun nanofibers, 23,24 hydrophilic colloids and hydrogels. 25–27 Among them, hydrogels show tremendous potential in wound healing therapy due to its unique extracellular matrix-like (ECM) three-dimensional (3D) structure, long-lasting moisturizing properties, and drug encapsulation capability.…”
Section: Introductionmentioning
confidence: 99%